Ukrainian Scientists in the War: Surviving and Being Useful - Iščuk-Pazunjak, Natalija (Occasional papers on religion in Eastern Europe, 2025)
"Russia’s war against Ukraine, which began in 2014 and escalated with the full-scale invasion in 2022, has wrought profound and tragic changes in Ukrainian society. The impact on scholars and university educators has been particularly significant, as they face numerous challenges affecting their safety, personal lives, and professional activities...Currently, the majority of scholars and university educators remain in Ukraine. Their conscious decision to endure the hardships of war alongside their people reflects their deep commitment to their homeland."